VqMYB154 promotes polygene expression and enhances resistance to pathogens in Chinese wild grapevine. (1st July 2021) - Jiang, Changyue; Wang, Dan; Zhang, Jie; Xu, Yan; Zhang, Chaohong; Zhang, Jianxia; Wang, Xiping; Wang, Yuejin
Abstract: Resveratrol plays a crucial phytoalexin role in the grapevine and is beneficial to human health. However, the molecular mechanism of resveratrol accumulation in the enhancement of disease resistance is unclear. Here, we report that the transcription factor VqMYB154 from Vitis quinquangularis accession Danfeng-2 is strongly expressed under artificial inoculation with Uncinula necator and regulates resveratrol accumulation. Unlike its homolog, VqMYB154 has a pathogen-induced promoter and responds to stimulation by U. necator, Pseudomonas syringae, and other treatments. Yeast one-hybrid and GUS activity assays confirmed that VqMYB154 can activate the stilbene synthase genes VqSTS9, VqSTS32, and VqSTS42 by directly binding to their promoters. Overexpression of VqMYB154 in grape leaves resulted in activation of the stilbene pathway, upregulation of STS genes, and accumulation of stilbenoids. In addition, heterologous overexpression of VqMYB154 in Arabidopsis activated resistance-related genes and resulted in greater programmed cell death and accumulation of reactive oxygen species, which led to resistance against P. syringae . These results suggest that the transcription factor VqMYB154 from V. quinquangularis accession Danfeng-2 participates in the regulatory mechanism that improves the biosynthesis and accumulation of stilbenes and enhances resistance to disease in grapevine.